2015
DOI: 10.1590/0104-07072015002760013
|View full text |Cite
|
Sign up to set email alerts
|

Nursing informatics: unveiling the computer use by nurses

Abstract: Study conducted with the objective of understanding the assistant nurses' perception of a philanthropic institution about the computer use at work. The data collection happened in January 2013, through interviews with 12 nurses who answered the question: tell me about the computer use at your work. The data were treated using the content analysis technique, in which emerged the following theme categories and subthemes: Realizing positive aspects on computer use (nine subthemes); Realizing negative aspects on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
6
0
4
Order By: Relevance
“…In the institutions that already use it, such as seen in the present study, it is possible to improve the use of computerized systems, by increasing the number of computers available for access (28) , employing more investment to avoid system failures (inoperative system) and in order to train and continue education, given that some health professionals still show resistance and difficulty to handle this type of documentation (27) . The mapping of 502 Nursing activities in North American hospitals (29) identified 21 of these as commonly being considered by 90% of nursing managers for daily decision making on Nursing staff.…”
Section: Discussionmentioning
confidence: 99%
“…In the institutions that already use it, such as seen in the present study, it is possible to improve the use of computerized systems, by increasing the number of computers available for access (28) , employing more investment to avoid system failures (inoperative system) and in order to train and continue education, given that some health professionals still show resistance and difficulty to handle this type of documentation (27) . The mapping of 502 Nursing activities in North American hospitals (29) identified 21 of these as commonly being considered by 90% of nursing managers for daily decision making on Nursing staff.…”
Section: Discussionmentioning
confidence: 99%
“…9) Notou-se também que os profissionais entrevistados sentem a necessidade de notebook ou tablets para serem levados para atendimentos externos, pois ainda fazem uso de fichas e cadernos. Os dispositivos móveis como smartphones e tablets são ferramentas que trazem benefícios quando utilizados na atenção primária, contudo, outros autores afirmam que a necessidade de grandes investimentos em equipamentos e treinamento é uma das desvantagens do PEP (17,18) . [ Mesmo no processo de trabalho dentro das unidades, percebeu-se que muitos ainda fazem uso de cadernos, pastas, entre outros sistemas de informação manuais, pois preferem ter anotações escritas acerca da sua área para controle.…”
Section: Acesso àS Informações -Confiabilidade E Qualidade Dos Dadosunclassified
“…[ Mesmo no processo de trabalho dentro das unidades, percebeu-se que muitos ainda fazem uso de cadernos, pastas, entre outros sistemas de informação manuais, pois preferem ter anotações escritas acerca da sua área para controle. Porém, é necessário salientar a importância de que os dados documentados de forma escrita sejam registrados também no PEP, uma vez que os registros no sistema de informação oficial contribuem não somente para a continuidade do cuidado ao paciente, a comunicação entre os diversos profissionais da saúde e a visibilidade das ações de cada profissional da equipe de saúde, mas também como um instrumento de proteção legal que converge com o cumprimento da responsabilidade ética do enfermeiro (18) . Os registros dos dados dos usuários vão além de quesitos relacionados à saúde, melhoria da qualidade e integração, mas também compõem quesitos éticos e legais.…”
Section: Acesso àS Informações -Confiabilidade E Qualidade Dos Dadosunclassified
See 1 more Smart Citation
“…However, in the decade of 2010 low availability of this class at undergraduate level has been observed, contrary to trends in the labor market and the National Curriculum Guidelines of the Nursing Undergraduate Courses, which determined the need to provide students with competencies and access to proper use of the new ICTs (5)(6) . This gap in the training of undergraduates may have caused consequences, as when considering the use of internet by Nursing students, research found they have informatics knowledge for academic use (7) and 58.3% of nurses at training, who had intermediate level of fluency in informatics, reported not having experienced the applicability of technologies in nursing practice during their training (8) .…”
Section: Introductionmentioning
confidence: 99%